Assessment of Fair Value Measurement for Financial Reporting in Industrial Manufacturing Firms in Nigeria - Ayeni-Agbaje, Abiodun Rafiat; Adesina, Olufemi Dadepo; Adebayo, Adesodun Isaac (The Journal of Accounting and Management, 2024)
Fair value measurement in financial reporting has become increasingly prevalent, marking a departure from traditional historical cost accounting. This study assesses the application of fair value measurement in industrial manufacturing firms in Nigeria, exploring its opportunities and challenges within the unique economic and regulatory context. The research employed content analysis of financial statements from seven listed industrial manufacturing companies in Nigeria, covering the period from 2013 to 2022. The findings reveal that fair value measurement is applied to varying degrees across financial instruments, property, plant and equipment, impairment assessments, investment property and intangible assets. Also, the study highlights the benefits of fair value measurement, including reflecting true economic value, enhancing transparency, facilitating better decision-making, mitigating risks, and attracting investment. However, challenges such as valuation complexity, subjectivity, illiquid markets, regulatory compliance, and potential volatility in reported financial results are also discussed. The study concludes that adherence to fair value accounting principles and observance of financial reporting qualities can enhance the usefulness of corporate financial reports for stakeholders.